Pemanfaatan Financial Technology bagi Pelaku UMKM Pada Masa New Normal di Provinsi Jambi - Edward Edward; Mohammad Ihsan; Ade Perdana Siregar (Universitas Batanghari Jambi, 2021)
The spread of the corona virus does not only have an impact on health but has an impact on the economic sector. Entering the new normal period, health protocols still have to be a concern because the Covid-19 pandemic has not ended. The development of MSMEs can make a positive contribution to the economy. The need for capital is the main reason for MSMEs to sustain their business. Capital is an important factor for business actors in building and developing their business. Knowledge, behavior, attitudes and beliefs about finance play an important role in making decisions, especially decisions about sources of venture capital. The government through regulations regarding financial technology provides solutions to answer the problems of MSME business actors during this new normal period. (1) Assessing the influence of financial literacy on decisions on the use of financial technology during the new normal period; (2) Assessing the influence of financial literacy on business actor confidence; (3) Assessing the influence between the trust of business actors on the decision to use financial technology in the new normal period; (4) Assessing the role of trust in business actors to be able to mediate the effect of financial literacy on decisions on the use of financial technology in the new normal period. The data analysis method used was the measurement of Structural Equation Modeling (SEM) using the SmartPLS software. The results showed that (1) financial literacy showed a significant positive effect on the decision to use financial technology during the new normal period; (2) financial literacy shows a significant positive effect on the trust of business actors; (3) the trust of business actors shows a significant positive effect on the decision to use financial technology during the new normal period; (4) the trust of business actors as a mediator of the effect of financial literacy shows a significant positive effect on decisions to use financial technology in the new normal period